2023
DOI: 10.3390/ani13132129
|View full text |Cite
|
Sign up to set email alerts
|

Hair Cortisol and Testosterone Concentrations in Relation to Maturity and Breeding Status of Male Feral Horses

Abstract: Steroid-hormone concentrations from non-invasively obtained biomarkers, like hair, can provide a representation of circulating hormones diffused over relatively long time periods (e.g., weeks or months). The hormone cortisol is often associated with physiological or even psychological stress, while testosterone is strongly associated with male development and reproductive success. Increasingly, studies are using hormone levels derived from hair to make inferences among both domestic animals and wildlife. For h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…, 2007 ). Another study showed that cortisol levels in reproductively competent adult male wild horses were negatively correlated with testosterone levels, while in non-reproductive males, they were positively correlated ( Medill et al. , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2007 ). Another study showed that cortisol levels in reproductively competent adult male wild horses were negatively correlated with testosterone levels, while in non-reproductive males, they were positively correlated ( Medill et al. , 2023 ).…”
Section: Discussionmentioning
confidence: 99%